To solve the equation y = -2x + 3, you need to find the value of x when given a specific value of y.
1. To find the value of x when y is known, substitute the given value of y into the equation. For example, if y = 4, then the equation becomes 4 = -2x + 3.
2. Rearrange the equation to isolate x. In the example above, you can do this by subtracting 3 from both sides of the equation to get 1 = -2x.
3. solve for x by dividing both sides by -2. This gives you x = -1/2.
Therefore, when y = 4 in the equation y = -2x + 3, x is equal to -1/2.
How to solve y = -2x + 3?
1 answer